1982
DOI: 10.1111/j.1600-0560.1982.tb01044.x
|View full text |Cite
|
Sign up to set email alerts
|

The nature of melanoma. A critical review

Abstract: The main object of this review was to examine the various histogenetic types of melanoma in order to determine their nature. Nodular melanoma and superficial spreading melanoma differ in the more rapid growth of the former. For tumors of equal depth of invasion in patients of the same sex, the prognoses are similar. Clinical features with prognostic significance are sex, age, and site of the lesion. Women have a decided superiority in survival up to the age of about 50 years when their superiority declines. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 64 publications
(71 reference statements)
2
24
1
1
Order By: Relevance
“…McGovern [2] has suggested that melanomas of histogenetic types other than superficial spreading, nodular, and lentigo maligna should be classified according to site rather than according to specific histology. There are several observations from the present series, supported in related literature, which suggest that acral melanomas should be treated as a clinical entity distinct from other extremity melanomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McGovern [2] has suggested that melanomas of histogenetic types other than superficial spreading, nodular, and lentigo maligna should be classified according to site rather than according to specific histology. There are several observations from the present series, supported in related literature, which suggest that acral melanomas should be treated as a clinical entity distinct from other extremity melanomas.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of subungual lesions was: thumb (17), index finger (3), long finger (5), ring finger (4), fifth finger (l), great toe (20), finger not specified (l), toe not specified (2). Eighty percent presented as stage I (local disease), 19% as stage I1 (lymph node metastases), and 1% as stage 111 (distant metastases).…”
Section: Description Of the Populationmentioning
confidence: 99%
“…Acral melanoma has relatively recently been defined as a melanoma of glabrous skin, which is the non-hair-bearing skin characteristic of the palmar, plantar and subungual regions and especially the dorsal area of the hand and the foot8,9. This is the most common subtype of cutaneous malignant melanoma in Asians, and this subtype of melanoma comprises a larger proportion in Asians in comparison to non-Asians.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of great interest to understand the mechanisms behind metastasis and develop better therapeutic targets [5], [12][17]. Melanoma, one type of tumor cells (TCs), is responsible for skin cancer which widely threatens human lives [18], [19]. Previous studies have indicated that human melanoma cells actively recruit leukocytes, especially neutrophils (PMNs), to adhere to the vascular endothelial cells (ECs) under high shear flow conditions, because the receptor-ligand bonds between melanoma cells and ECs were insufficient to enable initial capture of melanoma cells on vessel walls [20][26].…”
Section: Introductionmentioning
confidence: 99%